An alternative method for mucosal flap closure during peroral endoscopic myotomy using an over-the-scope clipping device - Saxena, P.; Chavez, Y. H.; Kord Valeshabad, A.; Kalloo, A. N.; Khashab, M. A. (Endoscopy, 2013)
Maintaining the integrity of the mucosal flap and the reliable closure of mucosal entry during peroral endoscopic myotomy (POEM) is paramount in preventing leakage of esophageal contents into the mediastinal space. We describe our experience with POEM, the problems encountered with closure of mucosal flaps, and successful closure with over-the-scope clips (OTSC). Two patients with achalasia underwent successful endoscopic myotomy during POEM. During both procedures, the proximal end of the longitudinal mucosal incision was noted to be gaping and completion of the closure with standard clips was unsuccessful. The sides of the flap were approximated using a Twin Grasper followed by placement of OTSC. Closure of the mucosal entry appeared to be complete at the end of the procedures. Esophagram the following day revealed no leaks in either patient. There were no other complications and patients were discharged home after 1 – 2 days of hospital observation. Patients reported complete resolution of achalasia symptoms during follow-up. We propose closure of mucosal incisions during POEM using one to two OTSC as an alternative to described techniques. The use of OTSC may simplify the procedure and result in a more durable (i. e. full-thickness) closure.